Loss of Cardiomyocyte Integrin-Linked Kinase Produces an Arrhythmogenic Cardiomyopathy in Mice. (August 2015) - Quang, Khai Le; Maguy, Ange; Qi, Xiao-Yan; Naud, Patrice; Xiong, Feng; Tadevosyan, Artavazd; Shi, Yan-Fen; Chartier, Denis; Tardif, Jean-Claude; Dobrev, Dobromir; Nattel, Stanley
<x xml:space="preserve">Abstract</x> Background— Integrin-linked kinase (ILK), a serine/threonine protein kinase, has roles in cell signaling and molecular scaffolding. ILK mutation/deletion causes cardiomyopathic phenotypes, but the functional and electrophysiological features have not been characterized. This study investigated the structural, functional, ion channel, and electrophysiological changes associated with cardiomyocyte-directed ILK deletion in mice. Methods and Results— Adult mice with cardiomyocyte-directed ILK knockout were compared with littermate controls. Knockout mice showed markedly increased mortality, with sudden death beginning after 5 weeks and 100% mortality at 18 weeks. In 10-week-old knockout mice, spontaneous and inducible ventricular tachyarrhythmias were common, occurring in 60% and 86%, respectively, and absent in controls (P<0.001, P<0.05 versus knockout mice). Ventricular refractoriness was prolonged, along with both QRS and QT interval. Action potentials were prolonged and displayed triggered activity. A wide range of ion currents were downregulated, including total, fast and slow components of transient outward K+ current and inward rectifier K+ current, along with corresponding ion channel subunit genes, providing a plausible explanation of action potential prolongation. At 5 weeks, only voltage-dependent K+ currents were reduced, possibly related to direct ILK-Kv4.2 subunit interactions. Action potentials were prolonged, but no arrhythmias or cardiac dysfunction were noted. Structural remodeling was prominent at 10 weeks: connexin-43 was downregulated and redistributed to lateral cell margins, and left ventricular fibrosis occurred, with a strong regional distribution (predominating in the basal left ventricle). Conduction was slowed. High-throughput quantitative polymerase reaction gene-expression studies in 10-week-old ILK knockout showed upregulation of structural, remodeling and fibrosis-related genes, and downregulation of a wide range of ion channel and transporter subunits. Conclusions— Cardiomyocyte ILK deletion produces a lethal arrhythmogenic cardiomyopathy associated with important ion channel and structural remodeling.